Autarky and Material Contingencies in Italian Architectural Debate (1936-1954) - Pep Avilés (Footprint)
On 3 October 1935, Mussolini’s fascist regime invaded Ethiopia with undesired but foreseeable consequences for its imperialist aims: four days after the conquest, the Society of Nations imposed economic sanctions, promoting an international economic blockade. This soon translated in both a control of foreign currencies in order to purchase iron and steel on the international markets, and a vociferous campaign discouraging the use of materials that were demanded by the military endeavour. Architecture as a discipline and all the industrial activity around it suffered from government directions as well as the scarcity and control of commodities. Hence, its discourse accommodated to the new material situation. National and autochthonous values came to the fore, promoting local materials like wood or stone for construction as well as artificial and newly created ones.